Dental curable composition

JP2025031494APending Publication Date: 2025-03-07TOKUYAMA DENTAL CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024039218
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-23
Filing Date
2024-03-13
Publication Date
2025-03-07

AI Technical Summary

Benefits of technology

【0014】 本発明の歯科用硬化性組成物は、流動性に優れ、光硬化深さが深く、硬化時の重合収縮応力が小さく、しかも高強度の硬化体を与えるというフロアブルタイプのバルクフィルCRに要求される特長を有する。また、構造色系CRとしても機能することに起因して、深い窩洞を修復したときにも色調適合性を示す。このため、本発明の歯科用硬化性組成物からなるCRを用いて臼歯部の深い窩洞を修復する際には、特に色の選択を要さずに1種のCRのみを用いた一括充填により、高度な審美修復が可能となる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025031494000001
    Figure 2025031494000001
  • Figure 2025031494000002
    Figure 2025031494000002
  • Figure 2025031494000003
    Figure 2025031494000003
Patent Text Reader

Abstract

To provide a dental curable composition that can be used as a flowable bulk fill CR and can perform aesthetic restoration by bulk filling.SOLUTION: A curable composition can give a cured body that exhibits a structural color by containing: a radical polymerizable monomer component (A) having a viscosity within a specific range; spherical inorganic powder particles (b) having a specific average particle size and particle size distribution, which are composed of spherical inorganic particles having a refractive index greater than that of the (A) and the cured body; and a photopolymerization initiator. A part of the (b) is blended with the remainder (B1) of (B) as powder particles (B2) composed of particles of a composite dispersed in a resin matrix having a refractive index smaller than that of the (b) and greater than that of the cured body of the (A) and having an average particle size and D90 within a specific range. Furthermore, the total blend amount of the (B1) and the (B2) and a blending ratio of the two are within a certain range.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a dental hardenable composition, specifically to a dental hardenable composition that can be suitably used as a flowable type bulk-fill composite resin. [Background technology]

[0002] In dental treatment, a dental filling material called dental composite resin (hereinafter, also simply referred to as "CR"), which is made of a hardenable composition containing a polymerizable monomer, a filler, and a polymerization initiator, is filled into a cavity after caries removal, and then hardened to seal the cavity with the hardened material (CR restoration). This type of CR restoration is rapidly becoming popular because it reduces the amount of tooth structure that needs to be removed, can impart a color tone equivalent to that of natural teeth, and is easy to operate. In recent years, due to the improvement in the mechanical strength of the hardened material and the improvement in adhesive strength with teeth, it is used not only for repairing anterior teeth, but also for molar teeth, which are subject to high occlusal pressure.

[0003] In actual CR repair, the fluidity and formability of CR that provides good operability differs depending on the specific mode of repair, so CRs with various properties are supplied to the market by various companies. In general, the surgeon who performs CR repair selects and uses the one that he or she judges to be suitable for the actual repair.

[0004] For example, CR is roughly divided into "universal composite resin" (a relatively hard paste with low fluidity that emphasizes formability) and "flowable composite resin" (one with fluidity that allows direct filling from a syringe) based on the difference in rough fluidity that affects operability during filling. Furthermore, for flowable composite resin (hereinafter also referred to as "flowable CR"), a type called "bulk fill type" (hereinafter also referred to as "bulk fill CR") has also been developed. Bulk fill CR is a light-cured CR that can be filled all at once into deep cavities, such as Class I molar cavities that are approximately 4 mm deep, to perform CR restoration. Flowable bulk fill CR is characterized by the fact that it contains a small amount of filler, giving it high fluidity that allows it to be filled all at once, that it is highly transparent to the light used for light curing (activation light for photopolymerization initiators) (deeper photocuring depth), and that it uses a filler made of granular powder composed of composite particles of resin and inorganic powder (hereinafter also referred to as "organic-inorganic composite filler") to reduce polymerization shrinkage.

[0005] Although flowable bulk-fill CR has such excellent features, it has been difficult to perform CR restoration with high aesthetics (reproducing the color tone of natural teeth) in deep cavities such as molar class I cavities by filling them all at once. This is because the color tone of teeth is not only observed as the color tone of the tooth surface (enamel part), but also as the color tone of the deeper layer (dentin part) that can be seen through is blended together to create a rich gradation. For this reason, in the case of aesthetic CR restoration of deep cavities, it was necessary to change the color tone of the hardening paste to be filled at certain depths and fill in layers to reproduce this subtle color tone, as in the case of using conventional (other than bulk-fill CR) flowable CR (see Non-Patent Documents 1 and 2).

[0006] In response to this situation, a bulk-fill CR has been proposed that allows relatively high-level aesthetic restoration by filling all at once by controlling the light scattering of the hardened material (so that the degree of diffusion: D defined by a certain formula is equal to or greater than a certain value) (see Patent Document 1). However, even in this case, it is necessary to prepare multiple types of bulk-fill CR with different shades, and select from them the material with the shade most similar to that of the tooth to be restored and the adjacent natural tooth for restoration.

[0007] Meanwhile, dental curable compositions have been proposed in recent years that use a filler made of spherical inorganic powder particles having a specific average particle size and particle size distribution, and the refractive index of the spherical inorganic powder particles is made larger than the refractive index of the resin portion that becomes the matrix when cured, thereby utilizing light interference, scattering, etc. to develop a structural color that develops in a predetermined color tone independent of the angle of incidence of light (hereinafter, dental curable compositions that develop such structural colors are also referred to as "structural color dental curable compositions") (see Patent Documents 2 and 3), and CRs made of such dental curable compositions (hereinafter, also referred to as "structural color CRs") have also been developed. The structural color dental hardenable composition (structural color CR) is known to have the following excellent features: (1) since it does not use dyes or pigments, it is unlikely to discolor over time; (2) it expresses a specific structural color tone that is not dependent on the angle of incidence of light depending on the average particle diameter of the spherical inorganic powder particles used; in particular, when spherical inorganic powder particles with an average primary particle diameter of 230 to 350 nm are used, it can be colored yellow to red, which is similar to the color of dentin; and (3) since the hardened body has a moderate transparency, it easily harmonizes with the color of the tooth to be restored, and it is possible to restore a wide range of colors of teeth to be restored with a single type of composite resin, with an appearance close to that of natural teeth, without the need for complicated shade taking or selection of the shade of the composite resin. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Patent No. 6966785 [Patent Document 2] International Publication No. 2020 / 050123 Brochure [Patent Document 3] Patent No. 6762623 [Patent Document 4] International Publication No. 2023 / 042598 Brochure [Non-patent literature]

[0009] [Non-Patent Document 1] Hideo Matsumura, Junji Tagami (eds.), "Adhesion Yearbook 2006", 1st edition, Quintessence Publishing Co., Ltd., August 2006, pp.129-137 [Non-Patent Document 2] "Science and Technique of Composite Resin Restorations" by Masashi Miyazaki, 1st Edition, Quintessence Publishing Co., Ltd., January 2010, p.48-49 Summary of the Invention [Problem to be solved by the invention]

[0010] The present invention aims to provide a dental hardenable composition that can be used as a flowable type bulk fill CR, and that can be used alone to perform aesthetic restoration by filling all at once, even for repairing deep cavities in molar teeth. [Means for solving the problem]

[0011] The present invention solves the above problems, and the first aspect of the present invention is A monomer component (A) which consists of one type of radically polymerizable monomer or a mixture of multiple radically polymerizable monomers and has a viscosity at 25°C of 100 to 500 mPa s; One or more "spherical particle groups of the same particle size" (B) are composed of inorganic spherical powder or granules (b) having an average primary particle size of 230 to 500 nm as measured by an electron microscope, and 90% or more of the total number of particles in the number-based particle size distribution of the powder or granules (b) are present within a range of 5% around the predetermined average primary particle size, and Photopolymerization initiator (C) Including, The number of "spherical particle groups of the same diameter" in (B) is a, and when a is 1, it is 1, and when a is 2 or more, it is a natural number from 1 to a. The variable m is a variable of the same diameter. Each "spherical particle group of the same diameter" is classified into B in order of the smallest average primary particle diameter. m and the refractive index for the sodium d line at 25°C is expressed as n, Each B when the a is 2 or more m The first condition is that the average primary particle diameters of the particles differ from each other by 25 nm or more; and The refractive index of the cured body (AP) of the above (A): n (AP) And each B m The refractive index of inorganic spherical powder (b) that constitutes the (Bm) When (Bm) Also, n (AP) <n (Bm) The second condition is that the relationship Satisfy both at the same time. The dental hardenable composition is a flowable composition capable of providing a hardened product that exhibits a structural color of a predetermined color tone independent of the angle of incidence of light, a part (B2F) of the inorganic spherical powder particles (b) which constitutes at least one type of "spherical particle group having the same particle size" constituting the (B) is contained in the dental curable composition as an organic / inorganic powder particle (B2) constituted of particles consisting of a complex in which the part of the inorganic spherical powder particles (B2F) is dispersed in a resin matrix (B2P); The (B2F) contained in each organic-inorganic composite particle constituting the (B2) is a part of inorganic spherical powder particles (b) constituting a single "spherical particle group of the same particle size", the average inorganic content defined by the total mass of the (B2F) relative to the total mass of the (B2) is 30 to 95 mass%, the median diameter in the volume-based particle size distribution of the (B2) determined by a laser diffraction-scattering method is 1 to 30 μm and D90 is less than 35 μm, Among the components (B) contained in the dental curable composition, the inorganic spherical powder contained in a non-organic-composite state other than the component (B2F) is designated as (B1), and the refractive index: n of the monomer component (A) is changed to n(A) For each organic-inorganic composite particle constituting the (B2), the refractive index: n of the (B2F) contained therein is set to n (B2F) The refractive index of (B2P): n is n (B2P) When Regarding (B1), which n (Bm) Also, n (A) <n (Bm) The relationship is established, For all of the organic-inorganic composite particles constituting the (B2), n (AP) <n (B2F) Relationship and n (B2P) <n (B2F) The relationship is established, the total content of the (B1) and the (B2) is 150 to 300 parts by mass relative to 100 parts by mass of the (A), and the proportion of the (B2) relative to the total amount of the (B1) and the (B2) is within the range of 50 to 70% by mass; The dental hardenable composition is characterized in that

[0012] The dental hardenable composition of the above embodiment (hereinafter also referred to as "dental hardenable composition of the present invention") further contains, as inorganic powder particles (D) consisting of inorganic particles other than the constituent particles of (B), 0.1 to 5 parts by mass of fine powder particles (D1) having an average primary particle diameter of 1 to 100 nm, relative to 100 parts by mass of (A); or further contains crystalline rare earth metal fluoride particles and having an average primary particle diameter of 1 to 300 nm as measured by electron microscopy. and further comprising rare earth metal fluoride powder (D2) having a full width at half maximum of a maximum intensity peak derived from the crystalline rare earth metal fluoride of 0.3° or more in an X-ray diffraction pattern obtained by X-ray diffraction measurement, the amount of (D2) is 5 to 25 parts by mass relative to 100 parts by mass of (A), and the total amount of (B1), (B2) and (D2) is 150 to 300 parts by mass relative to 100 parts by mass of (A).

[0013] A second embodiment of the present invention is a dental composite resin comprising the dental curable composition of the present invention, which has a photocuring depth of 3.5 to 5.0 mm as measured in accordance with JIS T6514:2015, and a fluidity of 4.0 to 12.0 mm as evaluated by the spreading diameter (mm) when a 0.1 g sample is placed in an area within a diameter of 5.5 mm on a horizontal glass plane and allowed to naturally spread at 37°C for 2 minutes. Effect of the Invention

[0014] The dental hardenable composition of the present invention has the characteristics required for a flowable bulk fill CR, such as excellent fluidity, deep photocuring depth, small polymerization shrinkage stress during curing, and a high-strength hardened product. In addition, since it also functions as a structural color CR, it shows color compatibility even when repairing deep cavities. Therefore, when repairing deep cavities in molars using the CR made of the dental hardenable composition of the present invention, it is possible to perform high-level aesthetic restoration by filling all at once using only one type of CR without the need to select a particular color.

[0015] Furthermore, the dental curable composition of the present invention has the advantage that sedimentation of coarse particles in the low viscosity monomer component is suppressed, and the fluidity of the paste is unlikely to change even after long-term storage.

[0016] Furthermore, the dental hardenable composition of the present invention further comprising a specific rare earth metal fluoride powder (D2) has, in addition to the above-mentioned excellent features, the feature of being able to impart high X-ray opacity to the hardened product. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] If the flowable type bulk fill CR could have the above-mentioned features of the structural color CR, it would be possible to solve the above-mentioned problems, but such a bulk fill CR is not known. For example, as described above, the bulk fill CR is characterized by the fact that it uses a small amount of filler and an organic-inorganic composite filler to increase fluidity and reduce polymerization shrinkage, and that it has a deep photocuring depth, but the fluidity, polymerization shrinkage, and photocuring depth of the structural color dental curable composition using the organic-inorganic composite filler specifically shown in Patent Documents 2 and 3 have not been particularly studied.

[0018] In order to solve the above problems, the present inventors have investigated the components and compositions of structural color dental curable compositions using organic-inorganic composite powder particles disclosed in Patent Documents 2 and 3. As a result, they have found that when the refractive index of the monomer and its cured product (polymer), the refractive index of the resin matrix in the organic-inorganic composite powder particles, and the refractive index of the spherical inorganic powder particles satisfy a specific relationship, the photocuring depth is deep, and when the total blend amount of the blended organic-inorganic composite powder particles and the (non-organic-inorganic composite) spherical inorganic powder particles and the blending ratio of the two are within a specific range, polymerization shrinkage can be suppressed and the strength of the cured product can be made practical. However, it has been found that the fluidity of such dental curable compositions can change when stored for a long period of time, which is probably due to the high fluidity. Therefore, in order to solve the above-mentioned new problems, further investigations were conducted, and as a result, it was found that the above-mentioned problems can be solved by controlling the particle size distribution of the organic-inorganic composite powder, and that when a certain amount of a specific X-ray contrast material is blended, X-ray contrast properties can be imparted to the cured product without impairing the above-mentioned physical properties, and thus the present invention was completed.

[0019] Thus, the dental curable composition of the present invention is characterized in that it can be suitably used as a flowable type bulk fill CR by selecting a system that satisfies specific conditions and further controlling the particle size distribution of the organic-inorganic composite powder particles from the structural color dental curable compositions using organic-inorganic composite powder particles disclosed in Patent Documents 2 and 3. Therefore, the dental curable composition of the present invention will be described in detail after explaining the structural color dental curable composition that is the premise of the dental curable composition of the present invention.

[0020] In this specification, unless otherwise specified, the expression "x~y" using the numerical values ​​x and y means "x or more and y or less". In the case where a unit is added only to the numerical value y in such an expression, the unit is also applied to the numerical value x. In addition, in this specification, the term "(meth)acrylic" means both "acrylic" and "methacrylic". Similarly, the term "(meth)acrylate" means both "acrylate" and "methacrylate", and the term "(meth)acryloyl" means both "acryloyl" and "methacryloyl". In addition, the refractive index means the refractive index for the sodium d line at 25°C.

[0021] 1. Structural color dental hardenable compositions As described above, the structural color dental hardenable composition is a dental hardenable composition containing a polymerizable monomer, a filler, and a polymerization initiator, which uses one or more "spherical particle groups of the same particle size" (B) consisting of spherical inorganic powder particles having a specific average particle size and particle size distribution as a filler, and by making the refractive index of the spherical inorganic powder particles larger than the refractive index of the resin part that becomes the matrix when hardened, it is possible to express a structural color that develops in a predetermined color tone independent of the angle of incidence of light by utilizing light interference and scattering, etc.

[0022] Here, "spherical particle group of the same particle size" (hereinafter sometimes abbreviated as "G-PID") means an aggregate of spherical inorganic particles consisting of inorganic spherical powder particles having a predetermined average primary particle size within the range of 100 to 1000 nm, in which 90% or more of the total number of particles in the number-based particle size distribution of the powder particles are present within a 5% range around the predetermined average primary particle size.

[0023] The individual inorganic particles constituting the powder or granule are preferably made of the same or substantially the same material. The average primary particle diameter is determined as follows by electron microscopy, i.e., by observation with a scanning electron microscope. That is, a photograph of the powder is taken at a magnification of 5,000 to 100,000 times with a scanning electron microscope (for example, "XL-30S" manufactured by Philips), the photographed image is processed using image analysis software (for example, "IP-1000PC", product name; manufactured by Asahi Kasei Engineering Co.), and the maximum diameter: x of each particle is determined for n particles (where n is a natural number of 30 or more) arbitrarily selected from 100 or more particles observed within a unit field of view. i (The unit is nm. i is a natural number from 1 to n.) is measured, and the sum is: Σx i From the following formula x AV =(Σx i ) / n x is calculated by AV means.

[0024] In addition, the term "spherical" does not necessarily mean a perfect sphere, but rather a nearly spherical shape, and specifically means that the average uniformity determined as follows is 0.6 or more, preferably 0.8 or more. That is, a photograph of the powder is taken with a scanning electron microscope, and the long diameter, which is the maximum diameter measured, of each of the n (a natural number ≧30) spherical particles observed within a unit field of view of the photograph is determined as L i The minor axis, which is the diameter perpendicular to the major axis, is B i When the ratio of the two for each particle (B i / L i ) Sum of Σ(B i / L i )from, Average symmetry = {Σ(B i / L i ) / n} means that the average uniformity determined by is 0.6 or more, preferably 0.8 or more.

[0025] The "spherical particles of the same particle size" (G-PID) in the present invention is basically the same as the "spherical particles of the same particle size" (G-PID) disclosed in Patent Document 2 and Patent Document 3, except that the average primary particle size is limited to a range of 230 to 500 nm.

[0026] In addition, the dental curable composition may contain one or more types of G-PID, at least one type of G-PID constituting one or more G-PIDs may be contained in the dental curable composition as an organic-inorganic powder constituted by particles of a composite in which a part of the inorganic spherical powder particles constituting the G-PID is dispersed in a resin matrix, and the following conditions (1) and (2) must be satisfied in order to express the above structural color, similarly to the structural color dental curable compositions disclosed in Patent Documents 2 and 3.

[0027] (1) The number of G-PIDs contained in the structural color dental hardenable composition is defined as a, and the spherical particles having the same particle size are classified into B and B in order of decreasing average primary particle size. m (However, m is 1 when a is 1, and is a natural number from 1 to a when a is 2 or more.) m The average primary particle diameters of the particles must differ from each other by 25 nm or more.

[0028] (2) The refractive index (at 25° C. for sodium d line) of the cured product of the polymerizable monomer: n (AP) And each B m The refractive index of the inorganic spherical powder particles that compose (Bm) When (Bm) Also, n (AP) <n (Bm) The condition that the relationship holds.

[0029] In addition, when the a is 2 or more, each B m The materials constituting the individual particles may be different from each other.

[0030] In addition, the difference (of 25 nm or more) in the average primary particle diameter in the above condition (1) is preferably 30 to 100 nm, particularly preferably 40 to 60 nm, and the number of G-PIDs contained in the dental hardenable composition: a is preferably 1 to 3, particularly preferably 1 or 2, and from the viewpoint of ease of production, is preferably 1.

[0031] In addition, Δn=n in the above condition (2) (Bm) -n (AP) The value is preferably 0.002 to 0.1, and particularly preferably 0.005 to 0.05.

[0032] Furthermore, from the viewpoint of reliably expressing the structural color, it is preferable that the arrangement structure of the inorganic spherical particles in the hardened product of the structural color dental hardenable composition has a short-range ordered structure that satisfies the following conditions 1 and 2, which is the same as in the structural color dental hardenable compositions disclosed in Patent Documents 2 and 3.

[0033] [Condition 1] In a radial distribution function graph showing the relationship between r / r0 and g(r) corresponding to r at that time, the x-axis is a dimensionless number (r / r0) normalized by dividing the distance r from the center of any inorganic spherical particle dispersed in the composite material by the average particle diameter r0 of all inorganic spherical particles dispersed in the composite material, and the y-axis is a radial distribution function g(r) representing the probability that other inorganic spherical particles are present at a point distant r from the center of any inorganic spherical particle. The nearest inter-particle distance r1, defined as the r corresponding to the peak top of the peak closest to the origin among the peaks appearing in the radial distribution function graph, is 1 to 2 times the average particle diameter r0 of all inorganic spherical particles dispersed in the composite material.

[0034] [Condition 2] When r corresponding to the peak top of the second closest peak from the origin among the peaks appearing in the radial distribution function graph is defined as the next nearest interparticle distance r2, the minimum value of the radial distribution function g(r) between the nearest interparticle distance r1 and the next nearest interparticle distance r2 is a value of 0.56 to 1.10.

[0035] Here, the radial distribution function g(r) is a well-known function for calculating the probability of the existence of another particle at a point a distance r away from any given particle, and is defined by the following equation (1).

[0036] g(r)={1 / <ρ>}×{dn / da}···(1) In the above formula (1), <ρ> represents the average particle density of particles in a plane, dn represents the number of particles present in the region between two circles with radii r and r+dr, centered on an arbitrary particle in the plane, and da represents 2πr·dr, which is the area of ​​the region. The above radial distribution function g(r) is generally expressed by a radial distribution function graph with distance r on the x-axis (distance axis) and the value of g(r) at r {the calculation result by the above formula (1)} on the y-axis (vertical axis), or by a radial distribution function graph with a dimensionless number normalized by dividing r by the average particle diameter of the particles on the distance axis and the value of g(r) at r corresponding to the x-axis value (the calculation result by the above formula) on the y-axis (vertical axis).

[0037] Because these conditions are easily satisfied, it is preferable to mix the "spherical particle group of uniform diameter" (G-PID) as aggregated particles having a median diameter of 5 μm to 200 μm, preferably 10 μm to 100 μm, in the volume-based particle size distribution determined by a laser diffraction-scattering method.

[0038] 2. Dental hardenable composition of the present invention The dental hardenable composition of the present invention, which is a structural color dental hardenable composition, satisfies the following conditions (A) to (F) and thus ensures suitable fluidity and photocuring depth as a flowable type bulk fill CR, and further inhibits changes in fluidity due to long-term storage.

[0039] (A) As the monomer component (A) corresponding to the polymerizable monomer of the structural color dental hardenable composition, a monomer component consisting of one type of radical polymerizable monomer or a mixture of multiple radical polymerizable monomers and having a viscosity of 100 to 500 mPa s at 25°C is used.

[0040] (A) A part (B2F) of the inorganic spherical powder particles (b) which constitutes at least one type of "same-particle-size spherical particle group" constituting one or more "same-particle-size spherical particle groups" (B) is contained in the dental curable composition as organic / inorganic powder particles (B2) which are composed of particles consisting of a complex in which the part of the inorganic spherical powder particles (B2F) is dispersed in a resin matrix (B2P). In other words, all of the inorganic spherical powder particles (b) which constitute (B) are divided into inorganic spherical powder particles (b) (B1) which are blended as they are, and organic / inorganic powder particles (B2) (B2F) which are blended as they are.

[0041] (c) Regarding (B1) above, each B m and the refractive index of the monomer component (A) have a specific relationship.

[0042] (D) Regarding (B2) above, (E1) The (B2F) contained in each organic-inorganic composite particle constituting the (B2) is a part of the inorganic spherical powder (b) constituting a single "spherical particle group of the same particle size", (D2) the average inorganic content defined as the total mass of (B2F) relative to the total mass of (B2) is 30 to 95 mass%, (D3) the refractive index of the inorganic spherical powder particles (B2F) in the organic / inorganic powder particles (B2) has a specific relationship with the refractive index of the monomer component (A) and the refractive index of the resin matrix (B2P), (E4) The median diameter and D90 in the particle size distribution are within specific ranges.

[0043] (E) The contents of (B1) and (B2) are within specific ranges.

[0044] (f) The blending ratio of (B1) and (B2) is within a specific range.

[0045] Below, these points (a) to (f) will be explained.

[0046] 2-1. Regarding (A) above In the dental curable composition of the present invention, a monomer component (A) is used that is composed of one type of radical polymerizable monomer or a mixture of multiple radical polymerizable monomers and has a viscosity of 100 to 500 mPa·s at 25°C. If the viscosity is less than 100 Pa·s, sedimentation of the organic-inorganic composite powder particles is likely to occur in the composition, and the fluidity of the paste is likely to change during long-term storage. If the viscosity exceeds 500 mPa·s, the fluidity of the composition (paste) is low, making it difficult to fill deep cavities (depth of about 4 mm) in molars. In addition, the viscosity is preferably 150 to 380 mPa·s, and particularly preferably 200 to 380 mPa·s, for the reason that the monomer mixture is easy to handle when kneading the paste using a kneader or the like.

[0047] The viscosity of the monomer component (A) can be confirmed by measuring it using a dynamic viscoelasticity measuring device generally called a rheometer. In the present invention, the viscosity was evaluated using a viscoelasticity measuring device CS rheometer "CVO120HR" (manufactured by Bohlin) equipped with a cone / plate geometry of 4 cm / 2° and a temperature control system at a measurement temperature (plate temperature) of 25°C and a shear rate of 1 rps, and the average value of three measurements was taken as the viscosity.

[0048] As the radical polymerizable monomer, any radical polymerizable monomer used in dental hardenable compositions can be used without any particular limitation as long as it satisfies the above conditions. In view of ease of handling and physical properties (mechanical properties and adhesiveness to tooth substance in dental applications) when used as a dental filling and restorative material, it is preferable to use a (meth)acrylic compound as the radical polymerizable monomer. Examples of (meth)acrylic compounds that can be suitably used include the following.

[0049] (i) Monofunctional (meth)acrylic compounds having no acidic or hydroxyl groups Methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-lauryl (meth)acrylate, n-stearyl (meth)acrylate, tetrafurfuryl (meth)acrylate, glycidyl (meth)acrylate, methoxyethylene glycol (meth)acrylate, and the like.

[0050] (ii) Monofunctional (meth)acrylic compound having an acidic group (Meth)acrylic acid, N-(meth)acryloylglycine, N-(meth)acryloylaspartic acid, N-(meth)acryloyl-5-aminosalicylic acid, 2-(meth)acryloyloxyethyl hydrogen succinate, 2-(meth)acryloyloxyethyl hydrogen phthalate, 2-(meth)acryloyloxyethyl hydrogen maleate, 6-(meth)acryloyloxyethyl naphthalene-1,2,6-tricarboxylic acid, O-(meth)acryloyltyrosine etc.

[0051] (iii) Monofunctional (meth)acrylic compound having a hydroxyl group 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, propylene glycol mono(meth)acrylate, glycerol mono(meth)acrylate, erythritol mono(meth)acrylate, N-methylol (meth)acrylamide, N-hydroxyethyl (meth)acrylamide, N,N-(dihydroxyethyl) (meth)acrylamide, etc.

[0052] (iv) Aromatic bifunctional (meth)acrylic compounds 2,2-bis(methacryloyloxyphenyl)propane, 2,2-bis[(3-methacryloyloxy-2-hydroxypropyloxy)phenyl]propane, 2,2-bis(4-methacryloyloxyphenyl)propane, 2,2-bis(4-methacryloyloxypolyethoxyphenyl)propane, 2,2-bis(4-methacryloyloxydiethoxyphenyl)propane, 2,2-bis(4-methacryloyloxytetraethoxyphenyl)propane, 2,2-bis(4-methacryloyloxypentaethoxyphenyl)propane, 2,2-bis[(4-methacryloyloxypolyethoxy)phenyl]propane, 2,2-bis(4-methacryloyloxydipropoxyphenyl)propane, 2(4-methacryloyloxydiethoxyphenyl)-2(4-methacryloyloxytriethoxyphenyl)propane and the like.

[0053] (v) Bifunctional (meth)acrylic compounds Ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, nonamethylene diol dimethacrylate, neopentyl glycol dimethacrylate, 1,3-butanediol dimethacrylate, 1,4-butanediol dimethacrylate, 1,6-hexanediol dimethacrylate, and the acrylates corresponding to these methacrylates; 2-hydroxyethyl methacrylate, 2,4-dimethylphenyl methacrylate, 1,6-bis(methacrylethyloxycarbonylamino)trimethylhexane, etc. Diaducts obtained from adducts of vinyl monomers having an -OH group, such as methacrylates such as 3-hydroxypropyl methacrylate and 3-chloro-2-hydroxypropyl methacrylate, or acrylates corresponding to these methacrylates, with diisocyanate compounds such as hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, diisocyanate methylcyclohexane, isophorone diisocyanate, and methylene bis(4-cyclohexyl isocyanate); 1,2-bis(3-methacryloyloxy-2-hydroxypropoxy)ethyl, and the like.

[0054] (vi) Trifunctional (meth)acrylic compound polymerizable monomer Methacrylates such as trimethylolpropane trimethacrylate, trimethylolethane trimethacrylate, pentaerythritol trimethacrylate, trimethylolmethane trimethacrylate, and acrylates corresponding to these methacrylates.

[0055] (vii) Tetrafunctional and bifunctional (meth)acrylic compounds Diaducts obtained from adducts of diisocyanate compounds such as pentaerythritol tetramethacrylate, pentaerythritol tetraacrylate, diisocyanate methylbenzene, diisocyanate methylcyclohexane, isophorone diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, methylene bis(4-cyclohexyl isocyanate), 4,4-diphenylmethane diisocyanate, and tolylene-2,4-diisocyanate with glycidol dimethacrylate, and the like.

[0056] If necessary, a radical polymerizable monomer other than the above (meth)acrylate monomer may be used.

[0057] It is preferable to set the type and amount of polymerizable monomer for monomer component (A) so that the refractive index for sodium d line at 25° C. is in the range of 1.38 to 1.55. That is, when a silica-titanium group element oxide based composite oxide, which has an easily adjustable refractive index, is used as the inorganic spherical powder material, the refractive index is in the range of about 1.45 to 1.58 depending on the silica content, as described below. However, by setting the refractive index of monomer component (A) in the range of 1.38 to 1.55, the refractive index of the obtained cured body can be adjusted to about 1.40 to 1.57, and n (AP) <n (Bm) In addition, when used as CR, the monomer component (A) is preferably composed of a (meth)acrylate monomer having no acidic group other than the above (ii).

[0058] 2-2. Regarding (a) above In the dental curable composition of the present invention, in order to ensure the strength of the cured product and further reduce polymerization shrinkage, a part (B2F) of the inorganic spherical powder particles (b) that constitutes at least one type of "spherical particle group of the same particle size" constituting one or more "spherical particle groups of the same particle size" (B) is included in the dental curable composition as organic inorganic powder particles (B2) that are composed of particles consisting of a complex in which the part of the inorganic spherical powder particles (B2F) is dispersed in a resin matrix (B2P). In other words, all of the inorganic spherical powder particles (b) that constitute (B) are divided into inorganic spherical powder particles (B1) that are inorganic spherical powder particles (b) that are blended as they are, and (B2F) that are blended as organic inorganic powder particles (B2).

[0059] As described above, each G-PID:B of one or more “spherical particle groups of the same particle size” (B) m The average primary particle diameter of the inorganic spherical powder particles (b) is set within the range of 230 to 500 nm from the viewpoint of developing a yellow to red structural color that is highly compatible with the surrounding dentin when the composition is used for repairing natural teeth, and from the viewpoint of increasing the light transmittance at 400 to 500 nm (purple to blue), particularly at 470 nm, irradiated during curing. From the viewpoints of the color tone of the developed structural color and the photocuring depth, the average primary particle diameter is preferably 240 to 450 nm, and most preferably 250 to 380 nm.

[0060] The material of the (spherical) inorganic particles constituting the inorganic spherical powder (b) is preferably a silica-based composite oxide, since the refractive index can be easily adjusted and, furthermore, since the particle surface has a large amount of silanol groups, it is easy to perform surface modification using a silane coupling agent, etc. From the viewpoint of X-ray contrast, silica-zirconia, silica-titania, silica-titania-barium oxide, silica-titania-zirconia, etc. are more preferable, and silica-zirconia is the most preferable because a hardened body with excellent wear resistance can be obtained. In addition, in the silica-titanium group element oxide composite oxide, the refractive index can be adjusted to a range of about 1.45 to 1.58 depending on the content of silica.

[0061] The spherical particles made of silica-titanium group element oxide-based composite oxide can be suitably manufactured by the so-called sol-gel method described in, for example, JP-A-58-110414, JP-A-58-151321, JP-A-58-156524, JP-A-58-156526, etc. The primary particle size can be controlled by reaction conditions such as reaction time. In order to impart surface stability to the spherical inorganic particles obtained by such a method, it is preferable to sinter them at a temperature of 500 to 1000°C after drying. During sintering, some of the inorganic particles may aggregate, so it is preferable to use a jet mill, a vibrating ball mill, etc. to disaggregate large aggregated particles into primary particles and small aggregated particles, and further adjust the particle size of the remaining aggregated particles to a predetermined range before use. Furthermore, it is preferable to surface-treat the spherical inorganic particles with a silane coupling agent, a titanate-based coupling agent, etc. The above surface treatment may be performed on the inorganic particles or on the inorganic aggregated particles. When inorganic agglomerated particles are produced by spray drying, it is efficient to carry out surface treatment at the same time as this treatment.

[0062] On the other hand, the organic inorganic powder (B2) can be suitably produced by a method according to the methods described in Patent Documents 2 and 3, in which inorganic aggregate particles formed by aggregation of inorganic spherical powder (B2F) are immersed in a solution containing a polymerizable monomer, a polymerization initiator, and an organic solvent, which are raw materials for the resin matrix (B2P), and then the organic solvent is removed and the polymerizable monomer is polymerized and cured by a method such as heating or light irradiation. According to such a method, an organic inorganic composite filler can be obtained in which the surfaces of each inorganic primary particle of the inorganic aggregate particles formed by aggregation of inorganic primary particles are covered with an organic resin phase that bonds each inorganic primary particle to each other, and an aggregate gap is formed between the organic resin phase that covers the surfaces of each inorganic primary particle. It is also possible to obtain the organic inorganic powder (B2) by a method in which predetermined amounts of each component of the inorganic spherical powder (B2F), the polymerizable monomer, and the polymerization initiator are mixed, polymerized by a method such as heating or light irradiation, and then pulverized. However, in either method, when a part of a plurality of types of "same particle diameter spherical particle group" (B) is to be organic-inorganic composited in order to satisfy the above condition (D1), it is necessary to produce an inorganic spherical powder (B2F) for each type of "same particle diameter spherical particle group" (B) and blend these individually or by mixing. In such a case, an aggregate of each inorganic spherical powder (B2F) constitutes the inorganic spherical powder (B2F) as a whole. In addition, the quantitative ratio of the inorganic spherical powder (B2F) and the polymerizable monomer that is the raw material of the resin matrix (B2P) is determined so as to satisfy the above condition (D2).

[0063] As the polymerizable monomer, it is preferable to use the same compound as the monomer component, and as the polymerization initiator, it is preferable to use a thermal polymerization initiator.

[0064] In the present invention, in order to obtain the desired effects, (B1) and (B2) must satisfy the above conditions (c) to (f).

[0065] 2-3. Regarding (U) above The refractive index of the monomer component (A): n (A) In the dental hardenable composition of the present invention, for (B1),m Refractive index: n (Bm) Also, n (A) <n (Bm) It is necessary to ensure that the following relationship is established.

[0066] When the above relationship is not satisfied, the refractive index of the cured body (AP) of (A): n is changed to n (AP) When (Bm) For n (AP) <n (Bm) In order to make it easier to satisfy the condition (2), the difference between the two refractive indices: {n (Bm) -n (A) The value of} is preferably 0.03 to 0.20, and particularly preferably 0.05 to 0.10.

[0067] 2-4. Regarding (D) above In the dental curable composition of the present invention, at least one type of "spherical particles having the same particle diameter" constituting (B) is blended as an organic-inorganic composite powder (B2) in which a part (B2F) of the inorganic spherical powder constituting the "spherical particles having the same particle diameter" is blended as an organic-inorganic composite powder (B2), as explained in (A) above. m In other words, in each organic-inorganic composite particle, all of the inorganic spherical powder particles dispersed in the resin matrix contain only a single G-PID (B m ) belonging to a single B m (B2) satisfies the condition (D1) that (B2) is a part of the inorganic spherical powder particles constituting (B2F) and (B2P) {However, (B2) may be composed of organic-inorganic composite particles of different types from (B2F) and / or (B2P).}. If the condition (D1) is not satisfied, it may be difficult to develop a structural color.

[0068] From the viewpoints of strength of the cured body and polymerization shrinkage suppression effect, the average inorganic content defined as the total mass of (B2F) relative to the total mass of (B2) must be 30 to 95 mass%, which satisfies the condition (D2). From the above viewpoints, the average inorganic content is preferably 50 to 90 mass%, more preferably 60 to 85 mass%.

[0069] In addition, the following conditions (D3) and (D4) must be satisfied.

[0070] Condition (E3): For all of the organic-inorganic composite particles constituting the (B2), n (AP) <n (B2F) Relationship and n (B2P) <n (B2F) The relationship is established. In addition, n (B2F) , n (AP) and n (B2P) respectively mean the refractive index of the inorganic spherical powder particles in each organic-inorganic composite particle, the refractive index of the resin matrix, and the refractive index of the cured product of the monomer component (A).

[0071] Condition (D4): The median diameter in the volume-based particle size distribution determined by the laser diffraction-scattering method in (B2) {hereinafter, also referred to as the "average particle size" in (B2)} is 1 to 30 μm, and D90 is less than 35 μm. Here, the median diameter means the particle diameter (D50) at the point where the cumulative % distribution curve in the above particle size distribution intersects with the horizontal axis at 50%, and D90 means the particle diameter at the point where it intersects with the horizontal axis at 90%, and is necessarily a value larger than the median diameter.

[0072] When the condition (E3) is not satisfied, the light having a short wavelength is likely to be interfered with, instead of the interference light due to the particle diameter according to the Bragg diffraction condition. In addition, in order to prevent the transparency of the hardened body of the dental hardenable composition of the present invention from being impaired as much as possible, the difference in refractive index: {n (B2F) -n (Ap)The value of {n} is preferably 0.002 to 0.1, particularly preferably 0.005 to 0.05. In order to prevent the light transmittance in the organic-inorganic composite particles from being impaired as much as possible, the difference in refractive index: {n (B2F) -n (B2p) The value of} is preferably 0.002 to 0.1, and particularly preferably 0.005 to 0.05.

[0073] The condition (2) that the structural color dental hardenable composition should satisfy: (AP) <n (Bm) Assuming that satisfies the above, n (AP) <n (B2F) The above relationship is naturally satisfied, so in order to satisfy the above condition (E3), it is only necessary to select and use a polymerizable monomer that satisfies the above condition as the raw material of the resin matrix (B2P) used in the production of (B2).

[0074] In addition, when the condition (D4) is not satisfied and the median diameter is less than 1 μm, it becomes difficult to increase the blending ratio of inorganic particles in the dental hardenable composition, polymerization shrinkage becomes large, and gaps are likely to occur on the cavity wall or cavity bottom when used as bulk fill CR. When it exceeds 30 μm, the organic-inorganic composite particles tend to settle in the dental hardenable composition, the fluidity changes significantly over time, and the discharge feeling tends to deteriorate. Furthermore, when D90 exceeds 35 μm, the organic-inorganic composite particles tend to settle in the dental hardenable composition, the fluidity changes significantly over time, and the discharge feeling tends to deteriorate.

[0075] In addition, when determining the volume-based particle size distribution by the laser diffraction-scattering method, a sample prepared by uniformly dispersing, for example, 0.1 g of the organic-inorganic composite powder (B2) in 10 mL of ethanol may be used.

[0076] 2-5. Regarding (E) and (F) above In the dental hardenable composition of the present invention, the total content of (B1) and (B2) relative to 100 mass parts of (A) is 150 to 300 mass parts, and further, the proportion of (B2) relative to the total amount of (B1) and (B2) needs to be within the range of 50 to 70 mass %.

[0077] If the total content of (B1) and (B2) is less than 150 parts by mass, the mechanical strength of the dental hardenable composition decreases and polymerization shrinkage increases, and if it exceeds 300 parts by mass, it becomes difficult to prepare a dental hardenable composition with high fluidity. For the reason that it becomes easier to prepare a bulk-fill type flowable CR, the total content is preferably 150 to 270 parts by mass, particularly 200 to 250 parts by mass.

[0078] If the ratio of (B2) to the total amount of (B1) and (B2) is less than 50% by mass, the dental curable composition will have a poorer discharge feeling, a lowered mechanical strength, and increased polymerization shrinkage, whereas if it exceeds 70% by mass, the specific surface area of ​​the inorganic particles in the dental curable composition will be smaller, the viscosity of the composition will be lowered, and the organic-inorganic composite particles will be more likely to settle. The ratio is preferably 55 to 70% by mass because it is easier to prepare a bulk-fill type flowable CR.

[0079] Next, the photopolymerization initiator and other optional components will be described.

[0080] 2-6. Photopolymerization initiator (C) In the dental hardenable composition of the present invention, a photopolymerization initiator is used as the polymerization initiator because it does not require a mixing operation and can be used in the oral cavity.

[0081] As the photopolymerization initiator (C), it is preferable to use a composition containing three components: a photosensitizing compound, a tertiary amine compound, and a photoacid generator. These components are explained below.

[0082] <Photosensitizing compound> The photosensitizing compound in the present invention is a compound that absorbs light of a wavelength of 400 nm to 500 nm emitted by a general dental light irradiator and generates an active species effective for polymerization. The active species is usually generated as a result of energy transfer or electron transfer between the photosensitizing compound excited by light absorption and a polymerizable monomer or other compound.

[0083] As the photosensitizing compound, known photosensitizing compounds can be used without any restrictions. As the photosensitizing compound particularly preferably used in the present invention, benzoin alkyl ethers such as benzoin methyl ether, benzoin ethyl ether, and benzoin isopropyl ether, benzil ketals such as benzil dimethyl ketal and benzil diethyl ketal, benzophenones such as benzophenone, 4,4'-dimethylbenzophenone, and 4-methacryloxybenzophenone, and α-diketones such as diacetyl, 2,3-pentanedione benzyl, camphorquinone, 9,10-phenanthraquinone, and 9,10-anthraquinone can be used.

[0084] Among the above compounds, α-diketones such as diacetyl, 2,3-pentanedione benzyl, camphorquinone, 9,10-phenanthraquinone, and 9,10-anthraquinone are more preferred.

[0085] The amount of the photosensitizing compound used is not particularly limited, but is usually 0.01 to 10 parts by mass, preferably 0.03 to 5 parts by mass, and more preferably 0.05 to 2 parts by mass, per 100 parts by mass of the polymerizable monomer (A).

[0086] <Tertiary amine compounds> As the tertiary amine compound, known tertiary amine compounds can be used without any restrictions. From the viewpoint of odor, etc., aromatic tertiary amine compounds are preferred. Examples of aromatic tertiary amine compounds that are preferably used in the present invention include N,N-dimethylaniline, N,N-dibenzylaniline, N,N-dimethyl-p-toluidine, N,N-diethyl-p-toluidine, methyl p-(N,N-dimethyl)aminobenzoate, ethyl p-(N,N-dimethyl)aminobenzoate, and amyl p-(N,N-dimethyl)aminobenzoate.

[0087] The tertiary amine compound may be an aliphatic tertiary amine compound, specifically, triethanolamine, N-methyldiethanolamine, triethylamine, tributylamine, N,N-dimethylaminoethyl methacrylate, N,N-diethylaminoethyl methacrylate, etc.

[0088] The amount of the tertiary amine compound used is not particularly limited, but is usually 10 parts by mass to 1,000 parts by mass, preferably 50 parts by mass to 500 parts by mass, and more preferably 75 parts by mass to 300 parts by mass, relative to 100 parts by mass of the photosensitizing compound.

[0089] <Photoacid generator> As the photoacid generator, a known photoacid generator can be used without any limitation. As the photoacid generator preferably used in the present invention, aryl iodonium salt compounds, sulfonium salt compounds, sulfonic acid ester compounds, s-triazine compounds having a halomethyl group as a substituent, pyridinium salt compounds, etc. can be mentioned, and in particular, aryl iodonium salt compounds or s-triazine compounds having a halomethyl group as a substituent are preferred.

[0090] For example, aryl iodonium salt compounds include salts composed of cations such as diphenyliodonium, bis(p-chlorophenyl)iodonium, ditolyliodonium, bis(p-methoxyphenyl)iodonium, bis(p-tert-butylphenyl)iodonium, p-isopropylphenyl-p-methylphenyliodonium, bis(m-nitrophenyl)iodonium, p-tert-butylphenylphenyliodonium, p-methoxyphenylphenyliodonium, p-octyloxyphenylphenyliodonium, and p-phenoxyphenylphenyliodonium, and anions such as nitrate, acetate, chloroacetate, carboxylate, and phenolate.

[0091] The amount of the photoacid generator used is not particularly limited, but is usually 10 parts by mass to 2000 parts by mass, preferably 20 parts by mass to 1000 parts by mass, and more preferably 50 parts by mass to 800 parts by mass, per 100 parts by mass of the photosensitizing compound.

[0092] 2-7. Other optional ingredients <Other inorganic powders (D)> The dental curable composition of the present invention may contain inorganic powder (D) consisting of inorganic particles other than the constituent particles of (B), preferably fine powder (D1) and / or rare earth metal fluoride powder (D2) described below.

[0093] <Fine powder (D1)> In the dental hardenable composition of the present invention, a very small amount of powder (fine powder): D1, which is made of inorganic particles other than the constituent particles of (B) and has an average primary particle size of 1 to 100 nm, may be blended for the purpose of adjusting the properties of the composition (paste) such as fluidity, or for the purpose of adjusting the translucency (contrast ratio) of the hardenable composition. The average primary particle size of the fine powder is preferably 3 to 75 nm, and more preferably 5 to 50 nm or less.

[0094] The inorganic particles constituting the fine powder can be made of the same material as in (B) without any particular restrictions. In addition, the surface treatment can be carried out with a silane coupling agent as in (B), and the preferred embodiments are basically the same as in (B) except for the average primary particle size.

[0095] The amount of the fine powder added is 0.1 to 5 parts by mass, more preferably 0.5 to 3 parts by mass, per 100 parts by mass of the monomer component (A). If the amount of the fine powder added exceeds the above range, the viscosity increases, and the composition may become a paste that is difficult to use as a flowable composite resin.

[0096] <Rare earth metal fluoride powder (D2)> The dental hardenable composition of the present invention preferably further contains rare earth metal fluoride powder (D2) which is composed of crystalline rare earth metal fluoride particles, has an average primary particle diameter of 1 to 300 nm as measured by electron microscopy, and has a full width at half maximum of the maximum intensity peak derived from the crystalline rare earth metal fluoride in an X-ray diffraction pattern obtained by X-ray diffraction measurement of 0.3° or more, because the dental hardenable composition can impart X-ray contrast properties to a hardened product thereof. The rare earth metal fluoride powder (D2) has been recently developed as a dental X-ray opaque filler capable of imparting X-ray contrast without reducing the transparency of the dental hardenable composition (see Patent Document 4). When D2 is blended into the dental hardenable composition of the present invention, from the viewpoint of imparting X-ray contrast without impairing the characteristics of the dental hardenable composition of the present invention, the blending amount is preferably 5 to 25 parts by mass relative to 100 parts by mass of (A), and the total content of (B1), (B2) and (D2) relative to 100 parts by mass of (A) is preferably 150 to 300 parts by mass. When the blending amount of (D2) is less than 5 parts by mass, it becomes difficult to obtain formability in a paste state, and when it exceeds 25 parts by mass, there is a risk of adversely affecting the expression of structural color. From the viewpoint of easily obtaining formability, hardening property, and color tone compatibility and transparency suitable for the dental hardenable composition, the blending amount is preferably 5 to 23 parts by mass, particularly 6 to 20 parts by mass. In addition, when the total content of (B1), (B2) and (D) is less than 150 parts by mass, the mechanical strength of the dental hardenable composition decreases and polymerization shrinkage increases, and when it exceeds 300 parts by mass, it becomes difficult to prepare a dental hardenable composition having flowability that allows direct filling from a syringe. For the reason that it becomes easy to prepare a bulk-fill type flowable CR, the total content is preferably 150 to 270 parts by mass, particularly 200 to 250 parts by mass.

[0097] As D2, similar to the dental X-ray opaque filler described in Patent Document 4, any powder or granule consisting of crystalline rare earth metal fluoride particles whose amorphous nature has been enhanced by, for example, mechanochemical treatment so that the full width at half maximum of the maximum intensity peak derived from the crystalline rare earth metal fluoride in the X-ray diffraction pattern is 0.3° or more can be used without any particular restrictions.

[0098] The average primary particle diameter of the crystalline rare earth metal fluoride particles constituting D2, as measured by electron microscope image analysis, is usually 1 to 300 nm, and from the viewpoint of aesthetics (e.g. polishability and transparency), it is preferably 10 to 300 nm, and more preferably 15 to 250 nm. Furthermore, the refractive index (for sodium d line at 25°C): n is preferably 1.4 to 1.7, from the viewpoint of transparency of the hardened body of the dental hardenable composition. The specific surface area of ​​D2, as measured by the nitrogen adsorption method, is 25 to 100 m 2 It is preferable that the molecular weight is in the range of / g.

[0099] The mechanochemical treatment is not particularly different from the method described in Patent Document 4, and a treatment using a wet bead mill, which is a treatment method in which a slurry of a powder to be treated and a medium is brought into contact with a medium (beads) that is given movement by stirring, vibration, or the like, to perform pulverization and / or crushing, can be suitably adopted, particularly a treatment using a cyclic bead mill or a pass-type bead mill. In this case, water or alcohol can be suitably used as the medium. In addition, it is preferable to use alumina or zirconia beads with a diameter of 0.01 to 0.5 mm as a material used as the medium (beads). The concentration of the slurry used in the mechanochemical treatment is preferably 100 parts by mass or less of inorganic particles per 100 parts by mass of the medium. In the treatment, a dispersant may be added to the slurry, such as glycerin fatty acid ester and its alkylene glycol adduct, aliphatic monocarboxylate, alkylamine salt, and alkylbetaine.

[0100] The crystallinity of the crystalline rare earth metal fluoride powder can be evaluated by the full width at half maximum of the maximum intensity peak derived from the crystalline rare earth metal fluoride in the X-ray diffraction pattern, and the smaller the full width at half maximum, the higher the crystallinity. Incidentally, the full width at half maximum of the maximum intensity peak of the rare earth metal fluoride generally used as an X-ray opaque material or the commercially available rare earth metal fluoride powder available as a raw material powder is usually less than 0.3° (specifically, about 0.12° to 0.27°), and when such rare earth metal fluoride powder is blended, the transparency is reduced. In order to obtain the effect of suppressing the decrease in transparency, the inorganic powder (d) consisting of rare earth metal fluoride particles obtained by the mechanochemical treatment needs to have a full width at half maximum of the maximum intensity peak derived from the crystalline rare earth metal fluoride in the X-ray diffraction pattern of 0.3° or more, and from the viewpoint of the effect of suppressing the decrease in transparency, the full width at half maximum of the maximum intensity peak is preferably 0.4° or more, particularly 0.5° or more. The upper limit of the full width at half maximum of the maximum peak is not particularly limited, but usually does not exceed 40°.

[0101] Here, the maximum peak full width at half maximum in the X-ray diffraction pattern can be determined by performing X-ray diffraction measurement on the inorganic powder (d) consisting of crystalline rare earth metal fluoride particles after mechanochemical treatment. Specifically, X-ray diffraction measurement is performed in the range of 2θ; 20 to 120° using an X-ray diffractometer, and the peaks derived from the crystalline rare earth fluoride in the obtained X-ray diffraction pattern (chart) with the horizontal axis being 2θ (°) and the vertical axis being diffraction intensity are identified, and the full width at half maximum of the peak having the maximum intensity (for example, for YbF3, the peak corresponding to the crystal plane (1,1,1) that appears around 2θ = 28.0°) is obtained, that is, the peak width at the intensity where the intensity is 50% of the peak intensity (maximum intensity) (the absolute value of the difference in 2θ between the two intersections of the intensity and the peak line: unit "deg [°]") can be determined. In addition, when making the measurement, it is preferable to remove coarse particles, for example by using a sieve with an opening of 100 μm, from the powder to be used as the measurement sample.

[0102] Furthermore, the mechanochemical treatment conditions vary depending on the operating method and bead diameter of the wet bead mill used, the maximum peak full width at half maximum of the crystalline rare earth metal fluoride, the concentration of the slurry, and other conditions. These conditions can be adjusted by conducting a preliminary experiment using the equipment and conditions for actually performing the mechanochemical treatment, and confirming the maximum peak full width at half maximum of the crystalline rare earth metal fluoride treated with the mechanochemical treatment time. During production, the treated slurry is sampled as necessary, and the maximum peak full width at half maximum is appropriately confirmed, thereby making it possible to reliably produce an X-ray impermeable filler having the desired maximum peak full width at half maximum.

[0103] <Chemical polymerization initiator> In the dental hardenable composition of the present invention, a chemical polymerization initiator may be used in combination with the photopolymerization initiator (C). As the chemical polymerization initiator, any known one that is composed of two or more components and generates a polymerization initiation species (radicals) when these components are brought into contact can be used without limitation. For example, those composed of various combinations such as organic peroxide / amines, organic peroxide / amines / organic sulfinic acids, organic peroxide / amines / aryl borates, aryl borates / acidic compounds, and barbituric acid derivatives / copper compounds / halogen compounds can be mentioned. Among these, those composed of organic peroxides / amines are particularly preferred because of their ease of handling.

[0104] As the organic peroxide, known hydroperoxides, peroxyketals, ketone peroxides, alkylsilyl peroxides, diacyl peroxides, peroxy esters, etc. can be used.

[0105] It is also a suitable embodiment that the chemical polymerization initiator consisting of this organic peroxide and the amine compound is further blended with a sulfinic acid such as benzenesulfinic acid, p-toluenesulfinic acid or a salt thereof, or a barbituric acid such as 5-butylbarbituric acid.

[0106] These polymerization initiators may be used alone or in combination of two or more. The amount of the polymerization initiator to be added may be selected from an effective amount depending on the purpose, and is usually 0.01 to 10 parts by mass, and preferably 0.05 to 2 parts by mass, per 100 parts by mass of the monomer component (A).

[0107] <Other additives> The dental hardenable composition of the present invention may contain other additives such as a polymerization inhibitor, an ultraviolet absorber, a fluorescent agent, an antioxidant, an antibacterial agent, and an X-ray contrast agent, as long as the effects of the composition are not impaired.

[0108] <Uses of the dental curable composition of the present invention> As shown in the examples below, the dental hardenable composition of the present invention includes compositions having a fluidity that can be used as a flowable CR, for example, a fluidity evaluated by the spread diameter (mm) when a 0.1 g sample placed in an area within a diameter of 5.5 mm on a horizontal glass plane is naturally spread at 37 ° C for 2 minutes, of 4.0 to 12.0 mm, and a photocuring depth that can be used as a bulk fill CR, for example, a photocuring depth measured according to JIS T6514:2015 of 3.5 to 5.0 mm. Therefore, it is suitably used as a photocurable flowable bulk fill composite resin. The dental hardenable composition of the present invention containing a predetermined amount of rare earth metal fluoride powder (D2) has a fluidity of about 4.0 to 8.0 mm, but the dental hardenable composition of the present invention not containing a predetermined amount of rare earth metal fluoride powder (D2) can have a fluidity of 9.0 to 12.0 mm.

[0109] Furthermore, the uses of the dental hardenable composition of the present invention are not limited thereto, and it can also be suitably used for other dental purposes, such as dental cement, restorative material for core construction, and the like. EXAMPLES

[0110] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0111] The dental curable compositions of the Examples and Comparative Examples were all prepared using the monomer component (A), the uniform particle size spherical particle group (B), the organic-inorganic composite powder (B2), and the photopolymerization initiator (C).

[0112] 1. Monomer component (A) The radical polymerizable monomers and radical polymerizable monomer mixtures (monomer components) M1 to M5 used in the examples and comparative examples are shown in Table 1. The abbreviations in the polymerizable monomer column in the table represent the following compounds, and the numbers in parentheses after the abbreviations represent the parts by mass used. UDMA: 1,6-bis(methacryloyloxycarbonylamino)trimethylhexane 3G: Triethylene glycol dimethacrylate D-2.6E: 2,2-bis[(4-methacryloyloxypolyethoxy)phenyl]propane ND: Nonamethylenediol dimethacrylate Bis-GMA: 2,2-bis[(3-methacryloyloxy-2-hydroxypropyloxy)phenyl]propane The viscosities and refractive indices of the above polymerizable monomers and M1 to M5 were evaluated by the following methods.

[0113] <Evaluation of Viscosity> The viscosity was measured using a CS rheometer under the following conditions: Using a viscoelasticity measuring device CS rheometer "CVO120HR" (manufactured by Bohlin) equipped with a cone / plate geometry of 4 cm / 2° and a temperature control system, the viscosity was evaluated at a measurement temperature (plate temperature) of 25°C and a shear rate of 1 rps, and the viscosity of the polymerizable monomer was calculated by calculating the average value of three measurements.

[0114] <Evaluation of refractive index> 1-1. [Refractive index of monomer component n (A) ] The refractive index n of the monomer components M1 to M5 used at 25° C. with respect to the sodium d line was measured in a thermostatic chamber at 25° C. using an Abbe refractometer (manufactured by Atago Co., Ltd.).

[0115] <Refractive index n of polymer (cured product) of monomer component (AP) > The refractive index n of the polymers of the monomer components M1 to M5 used was measured in a thermostatic chamber at 25° C. using an Abbe refractometer (manufactured by Atago Co., Ltd.) for the polymers polymerized under substantially the same conditions as those in the cavity.

[0116] That is, a homogeneous polymerizable monomer (or a mixture of polymerizable monomers) containing 0.2% by mass of camphorquinone (CQ), 0.3% by mass of ethyl pN,N-dimethylaminobenzoate (DMBE), 0.4% by mass of diphenyliodonium-2-carboxylate monohydrate (DPIC), and 0.15% by mass of hydroquinone monomethyl ether (HQME) was placed in a mold having a through hole of φ7 mm × depth 0.5 mm, and polypropylene films were pressed onto both sides. Then, the sample was exposed to a light intensity of 800 mW / cm. 2 The sample was irradiated with light for 30 seconds using a halogen-type dental light irradiator (Demetron LC, manufactured by Cybron) to harden it, and then removed from the mold to prepare a polymer of the polymerizable monomer. When the polymer was set in an Abbe refractometer (manufactured by Atago Co., Ltd.), a solvent (1-bromonaphthalene) that does not dissolve the sample and has a higher refractive index than the sample was dropped onto the sample for the purpose of adhering the polymer to the measurement surface.

[0117] [Table 1]

[0118] 2. Group of spherical particles with the same particle size (B) 2-1. [Inorganic powders and their production] The inorganic spherical powder particles (b): F1 to F4 constituting the uniform particle diameter spherical particle group (B) were prepared by the so-called sol-gel method described in JP-A-58-110414, JP-A-58-156524, etc., by adding a mixed solution containing a hydrolyzable organosilicon compound (tetraethyl silicate) and a hydrolyzable organotitanium group metal compound (tetrabutyl zirconate or tetrabutyl titanate) to an ammoniacal alcohol solution containing ammonia water, hydrolyzing the mixture to precipitate a reaction product, and then drying, pulverizing, and calcining the mixture.

[0119] The inorganic irregular powder and granule F5 composed of crushed inorganic particles (inorganic particles having an irregular shape obtained by crushing or pulverization) was prepared according to the method described in JP-A-2-132102, JP-A-3-197311, etc., by dissolving an alkoxysilane compound in an organic solvent, adding water to the solution to cause partial hydrolysis, and then adding an alkoxide of another metal to be composited and an alkali metal compound to cause hydrolysis to produce a gel-like substance, and then drying the gel-like substance, followed by pulverization and calcination as necessary.

[0120] The analytical results of inorganic powder particles (spherical inorganic powder particles and amorphous inorganic powder particles) F1 to F5 used in the examples are shown in Table 2. The average particle size of F1 to F5 means the average primary particle size explained in 2-2. The refractive index n for the sodium d line at 25°C was measured by the liquid immersion method using an Abbe refractometer (manufactured by Atago Co., Ltd.). That is, in a thermostatic chamber at 25°C, the inorganic powder particles were dispersed in 50 mL of anhydrous toluene in a 100 mL sample bottle. While stirring this dispersion with a stirrer, 1-bromotoluene was added dropwise little by little, and the refractive index of the dispersion liquid at the point when the dispersion liquid became most transparent was measured, and the obtained value was taken as the refractive index of the inorganic powder particles.

[0121] [Table 2]

[0122] 2-2. [Production of organic-inorganic composite powder: CF1] 100 g of the inorganic spherical powder (F1) shown in Table 2 was added to 200 g of water, and an aqueous dispersion of these was obtained using a circulation type grinding machine SC Mill (manufactured by Nippon Coke and Engineering Co., Ltd.). On the other hand, 4 g (0.016 mol) of γ-methacryloyloxypropyltrimethoxysilane and 0.003 g of acetic acid were added to 80 g of water and stirred for 1 hour and 30 minutes to obtain a homogeneous solution with a pH of 4. This solution was added to the dispersion of the inorganic spherical powder particles and mixed until homogeneous. After that, the dispersion was lightly mixed and fed onto a disk rotating at high speed to be granulated by spray drying. The spray drying was carried out using a spray dryer TSR-2W (manufactured by Sakamoto Giken Co., Ltd.) equipped with a rotating disk and atomizing by centrifugal force. The disk rotation speed was 10,000 rpm, and the temperature of the drying atmosphere air was 200° C. The powder obtained by granulation through spray drying was then vacuum-dried at 60° C. for 18 hours, yielding 73 g of powder (agglomerated powder) composed of roughly spherical aggregated particles.

[0123] Next, 50 g of the aggregated powder was immersed in a polymerizable monomer solution (containing 36 parts by mass of polymerizable monomer per 100 parts by mass of organic solvent) containing 10 g of UDMA as a polymerizable monomer, 0.025 g of azobisisobutyronitrile (AIBN) as a thermal polymerization initiator, and 5.0 g of methanol as an organic solvent. After thorough stirring, the mixture was confirmed to be in a slurry state, and then allowed to stand for 1 hour.

[0124] The mixture was transferred to a rotary evaporator. The mixture was dried for 1 hour under stirring conditions at a reduced pressure of 10 hectopascals and at a heating condition of 40°C (using a hot water bath) to remove the organic solvent. After the organic solvent was removed, a powder with high fluidity was obtained. The obtained powder was heated for 1 hour under conditions of a vacuum degree of 10 hectopascals and heating conditions of 100°C (using an oil bath) while stirring in a rotary evaporator, thereby polymerizing and hardening the polymerizable monomer in the powder. This operation yielded 145 g of organic-inorganic composite powder: CF, which is composed of approximately spherical organic-inorganic composite particles in which the surfaces of spherical aggregates are covered with an organic polymer. When the average particle size and D90 of this organic-inorganic composite powder were evaluated by the method described below, the average particle size (median diameter in the volume-based particle size distribution) was 40 μm and the D90 was 45 μm, which did not satisfy the above condition (E4).

[0125] <Evaluation of average particle size and D90 of organic-inorganic composite powders> 0.1 g of organic-inorganic composite powder was dispersed in 10 mL of ethanol and irradiated with ultrasonic waves for 20 minutes. Using a particle size distribution analyzer "LS230" (manufactured by Beckman Coulter) using the laser diffraction-scattering method, the average particle size and D90 were calculated from the median diameter of volume statistics by applying the optical model "Fraunhofer."

[0126] 2-3. [Production of organic-inorganic composite powder: CF2] The above-mentioned organic inorganic composite powder (CF1) was prepared in the same manner as above until the polymerizable monomer in the organic inorganic composite powder was polymerized and cured, and then the mixture was sieved for 30 minutes using a stainless steel sieve with a mesh size of 45 μm, and the residue was collected. By this operation, 32 g of organic inorganic composite powder (CF2) was obtained, which is approximately spherical and has an average particle size of 20 μm and a D90 of 25 μm, and satisfies the above-mentioned condition (E4).

[0127] 3. Polymerization initiator The polymerization initiator used was a photoinitiator consisting of a combination of camphorquinone (CQ), ethyl pN,N-dimethylaminobenzoate (DMBE), diphenyliodonium-2-carboxylate monohydrate (DPIC) and hydroquinone monomethyl ether (HQME).

[0128] 4. Fine powder As the fine powder, S1: Reolosil QS-102 (average primary particle size 12 nm, manufactured by Tokuyama Corporation) was used.

[0129] 5.Rare earth metal fluoride powder (D2) By carrying out mechanochemical treatment on each crystalline rare earth metal fluoride powder (YbF3, CeF3, GdF3 and LaF3), four types of rare earth metal fluoride powders: FX1 to FX4, each having an average primary particle diameter of 1 to 300 nm measured by electron microscopy and a full width at half maximum of the maximum intensity peak derived from the crystalline rare earth metal fluoride of 0.3° or more in the X-ray diffraction pattern obtained by X-ray diffraction measurement, were prepared. The mechanochemical treatment was carried out by dispersing a slurry obtained by mixing 5.0 parts by mass of each crystalline rare earth metal fluoride powder with 100 parts by mass of ion-exchanged water using a wet bead mill SC50 {manufactured by Mitsui Mining Co., Ltd.}, using 100 g of φ0.3 mm zirconia beads as a medium, at a rotation speed of 3000 rpm for the treatment time shown in Table 3. The obtained slurry was dried under reduced pressure using an evaporator to obtain a white solid. The obtained solid was pulverized in a mortar, and then coarse particles were removed using a comb with 100 μm openings to obtain powders, which were used as various inorganic fillers.

[0130] For FX1 to FX4 thus obtained, the 2θ and full width at half maximum (deg:°) of the peak of the crystal plane (1,1,1) in the X-ray diffraction pattern were measured as follows. The results are shown in Table 3.

[0131] <Measuring method for 2θ and full width at half maximum (deg:°) of crystal plane (1,1,1)> Various powders and granules were loaded onto a sample stage and measured using an X-ray diffractometer (Rigaku Corporation's "Smartlab"). From the obtained X-ray diffraction pattern (chart), the horizontal axis is 2θ (°) and the vertical axis is diffraction intensity, and the 2θ and full width at half maximum (deg:°) of the peak of the crystal plane (1,1,1) were read.

[0132] <Method for measuring average primary particle size> Photographs of the powder were taken at magnifications of 5,000 to 100,000 times using a scanning electron microscope (Philips "XL-30S"), and the images were processed using image analysis software ("IP-1000PC", product name; Asahi Kasei Engineering Co., Ltd.). The average primary particle size was calculated based on the measured value of the number of particles (30 or more) observed within a unit field of view of the photograph.

[0133] [Table 3]

[0134] Example 1 To 100 parts by mass of polymerizable monomer M1, 0.2 parts by mass of CQ, 0.3 parts by mass of DMBE, 0.4 parts by mass of DPIC, and 0.15 parts by mass of HQME were added and mixed to prepare a uniform polymerizable monomer composition. Next, 200 parts by mass of organic-inorganic composite powder CF2 and 100 parts by mass of inorganic powder F1 were weighed out, and the above polymerizable monomer composition was gradually added under red light, and kneaded using a planetary mixer (manufactured by Inoue Seisakusho) to obtain a uniform curable paste. Furthermore, this paste was degassed under reduced pressure to remove air bubbles, and a polymerizable curable composition was produced. The obtained polymerization curable composition was filled into a syringe container, and (1) the fluidity immediately after production and after 6 months of storage at 37 ° C, (2) the consistency immediately after production and after 6 months of storage at 37 ° C, and (3) the discharge feeling immediately after production and after 6 months of storage at 37 ° C, (4) the photocuring depth of the curable composition (paste), (5) the light transmittance of the curable composition (cured product) at a wavelength of 470 nm, (6) the polymerization shrinkage stress, (7) the bending strength, (8) the visual evaluation of the colored light, (9) the wavelength of the colored light, and (10) the visual evaluation of the color tone compatibility were performed. The composition of the curable composition (paste) is shown in Table 4, and the evaluation results are shown in Tables 5 to 7. The above evaluations and measurements were carried out by the methods described below.

[0135] (1) Liquidity assessment A needle tip with an inner diameter of 0.75 mm was attached to the tip of the syringe container, and 0.1 g of paste was discharged from the tip of the needle tip into an area within a circle with a diameter of 5.5 mm on a glass plate (5 cm x 10 cm) by pressing the plunger (so that the tip of the needle tip does not deviate from the vertical line passing through the center of the circle as much as possible). After keeping the plate in a 37°C incubator for 120 seconds, the plate was exposed to light with a light intensity of 800 mW / cm. 2 After the resin was cured by irradiation with light for 30 seconds using a halogen-type dental light irradiator (Demetron LC, manufactured by Cybron), the vertical diameter (vertical diameter) and horizontal diameter (horizontal diameter) of the obtained cured product were measured, and the following formula was calculated based on the measured values: Fluidity [mm] = (vertical diameter + horizontal diameter) / 2 The fluidity of the paste was calculated by the above formula. The fluidity was evaluated twice, and the average value was regarded as the fluidity of the paste.

[0136] (2) Evaluation of consistency In a temperature-controlled room at 25°C, 0.2 g of paste was discharged from the tip of the syringe container onto a region within a circle with a radius of 5.5 mm on a polypropylene film (5 cm x 5 cm), and a polypropylene film (5 cm x 5 cm) and a 50 g weight were placed on top of it and pressed for 10 seconds. After that, the pressed paste was exposed to a light intensity of 800 mW / cm. 2 The resin was cured by irradiating the resin with light for 30 seconds using a halogen-type dental light irradiator (Demetron LC, manufactured by Cybron). The vertical diameter (vertical diameter: twice the vertical radius) and horizontal diameter (horizontal diameter: twice the horizontal radius) of the obtained cured product were measured, and the following equation was calculated based on the measured values: Consistency [mm] = (vertical diameter + horizontal diameter) / 4 The consistency of the paste was calculated by the above formula. The consistency was evaluated twice, and the average value was used as the consistency of the paste.

[0137] (3) Evaluation of feeling of discharge A needle tip with an inner diameter of 0.75 mm was attached to the tip of the syringe container, and 0.2 g of paste was discharged from the tip of the needle tip onto a glass plate (5 cm x 10 cm) by pressing the plunger. The ease of pressing the plunger at this time was confirmed, and the discharge feel of the paste was evaluated according to the following evaluation criteria. Note that a discharge feel of 1 to 3 was considered to be an acceptable product. 1: The paste can be ejected even when pressed lightly, and ejection properties are very good. 2: The paste can be discharged without difficulty and has good discharge properties. 3: The paste can be ejected by pressing with some force, and ejection properties are acceptable. 4: The paste can be ejected if pressed forcefully, but ejection is poor. 5: No paste can be dispensed at all.

[0138] (4) Evaluation of photocuring depth In accordance with JIS T6514:2015, the paste was dispensed from the syringe container into a SUS split mold with a hole of φ4 mm × depth 10 mm, and the mold was pressed with a polypropylene film. A light intensity of 800 mW / cm was applied from above. 2 After 30 seconds of light irradiation using a halogen type dental light irradiator (Demetron LC, manufactured by Cybron Co., Ltd.) to cure the paste, the cured product was removed from the mold, the uncured paste was removed with a spatula, and the thickness of the cured part was measured with a micrometer, and half of the measured value was regarded as the photocuring depth. The test was performed three times, and the average value was evaluated as the photocuring depth.

[0139] (5) Evaluation of light transmittance The paste was discharged from the syringe container into a polyacetal mold with a hole of φ20 mm × depth 0.5 mm, and pressed against the mold with a polypropylene film. A light intensity of 800 mW / cm was applied from above. 2 The product was cured by irradiating it with light for 30 seconds using a halogen-type dental light irradiator (Demetron LC, manufactured by Cybron Co., Ltd.), and then the cured product was removed from the mold, and the transmittance of the resulting cured product at a wavelength of 470 nm was evaluated using a color difference meter "SE7700" (manufactured by Nippon Denshoku Co., Ltd.) The test was performed three times, and the average value was evaluated as the light transmittance.

[0140] (6) Evaluation of polymerization shrinkage stress In a jig connected to a universal tensile testing machine Autograph (Shimadzu Corporation), One-Up Bond F Plus (Tokuyama Dental Co., Ltd.) was applied to the top surface of a rod with a diameter of 6 mm, and the light intensity was 800 mW / cm 2 After irradiating the cavity with light for 10 seconds using a halogen-type dental light irradiator (Demetron LC, manufactured by Cybron), a ring was placed over the cavity to create a simulated cavity with a depth of 4 mm. The paste was discharged from the syringe container and filled into the simulated cavity, and visible light was irradiated for 30 seconds using the halogen-type dental light irradiator. At this time, the crosshead fixing the load cell started to move downward due to polymerization shrinkage of the curable composition, and the minute movement was detected by the displacement detector of the load cell, and the detected force was taken as the polymerization shrinkage stress of the curable composition. The test was performed three times, and the average value was used for evaluation.

[0141] (7) Evaluation of bending strength The paste was discharged from the syringe container into a SUS mold with a hole of 2 mm width, 2 mm thickness, and 25 mm length, and was then pressed against the mold with a polypropylene film. A light intensity of 800 mW / cm was applied from above. 2 Using a halogen-type dental light irradiator (Demetron LC, manufactured by Cybron), the specimen was irradiated for 30 seconds at three points on one side, changing the location so that the entire specimen was irradiated with light, and then turned over and irradiated in the same way. After hardening, the specimen was removed from the mold and immersed in water at 37°C for 24 hours. The specimen was then taken out of the water and polished in the longitudinal direction with waterproof abrasive paper #1500 to obtain a specimen with a width of 2±0.1 mm and a thickness of 2±0.1 mm. Using a universal tensile testing machine Autograph (Shimadzu Corporation), a three-point bending test was performed in air at room temperature with a support distance of 20 mm and a crosshead speed of 1 mm / min. The test was performed on five test pieces, and the average value was evaluated as the bending strength.

[0142] (8) Visual evaluation of colored light The paste was discharged from the syringe container into a polyacetal mold with a hole of φ7 mm × depth 1 mm, and pressed against the mold with a polypropylene film. A light intensity of 800 mW / cm was applied from above.2 After hardening for 30 seconds by irradiation with light using a halogen-type dental light irradiator (Demetron LC, manufactured by Cybron), the hardened body was removed from the mold and placed on the adhesive surface of a piece of black tape (carbon tape) approximately 10 mm square, and the color tone of the colored light was confirmed visually.

[0143] (9) Evaluation of wavelength of colored light The cured product prepared in the above test (8) was placed on the adhesive surface of a black tape (carbon tape) of about 10 mm square, and the spectral reflectance was measured using a color difference meter "SE7700" (manufactured by Nippon Denshoku Co., Ltd.), and the maximum value of the reflectance of light on a black background was taken as the wavelength of the colored light. The test was performed three times, and the average value was evaluated as the wavelength of the colored light.

[0144] (10) Visual evaluation of color compatibility Using a hard resin tooth that reproduced a Class I cavity (diameter 4 mm, depth 3.5 mm) in the center of the occlusal surface of the lower right number 6, a hardenable composition was filled into the missing area, which was then hardened and polished. The color compatibility was visually confirmed and evaluated on a 5-point scale from 1 to 5 as shown below. 1: The color of the restoration is indistinguishable from that of hard resin teeth. 2: The color of the restoration matches well with the hard resin teeth. 3: The color of the restoration is similar to that of the hard resin tooth. 4: The color of the restoration is similar to that of the hard resin tooth, but the fit is not good. 5: The color of the restoration does not match the hard resin tooth.

[0145] For the hard resin teeth, high saturation hard resin teeth (equivalent to A4) and low saturation hard resin teeth (equivalent to A1) in the A series (reddish brown) category of the shade guide ("VITA Classical", manufactured by VITA Co., Ltd.) were used, as well as high saturation hard resin teeth (equivalent to B4) and low saturation hard resin teeth (equivalent to B1) in the B series (reddish yellow) category of the shade guide ("VITA Classical", manufactured by VITA Co., Ltd.).

[0146] [Table 4]

[0147] [Table 5]

[0148] [Table 6]

[0149] [Table 7]

[0150] Examples 2 to 7 In Example 1, a curable composition was produced in the same manner as in Example 1, except that the composition of the curable composition was shown in Table 4, and filled into a syringe container. (1) Evaluation of fluidity immediately after production and after 6 months of storage at 37 ° C, (2) Evaluation of consistency immediately after production and after 6 months of storage at 37 ° C, and (3) Evaluation of discharge feeling immediately after production and after 6 months of storage at 37 ° C, (4) Evaluation of photocuring depth of the curable composition (paste), (5) Evaluation of light transmittance at a wavelength of 470 nm of the curable composition (cured product), (6) Evaluation of polymerization shrinkage rate, (7) Evaluation of bending strength, (8) Evaluation of colored light by visual observation, (9) Evaluation of wavelength of colored light, and (10) Evaluation of color tone compatibility by visual observation were performed. The evaluation results are shown in Tables 5 to 7.

[0151] Comparative Examples 1 to 6 In Example 1, a curable composition was produced in the same manner as in Example 1, except that the composition of the curable composition was shown in Table 4, and filled into a syringe container. (1) Evaluation of fluidity immediately after production and after 6 months of storage at 37 ° C, (2) Evaluation of consistency immediately after production and after 6 months of storage at 37 ° C, (3) Evaluation of discharge feeling immediately after production and after 6 months of storage at 37 ° C, (4) Evaluation of photocuring depth of the curable composition (paste), (5) Evaluation of light transmittance at a wavelength of 470 nm of the curable composition (cured product), (6) Evaluation of polymerization shrinkage stress, (7) Evaluation of bending strength, (8) Evaluation of colored light by visual observation, (9) Evaluation of wavelength of colored light, and (10) Evaluation of color tone compatibility by visual observation were performed. The evaluation results are shown in Tables 5 to 7.

[0152] As can be seen from the results of Examples 1 to 7, the dental curable composition of the present invention showed little change in fluidity even after storage at 37°C for 6 months, and maintained the paste properties at the time of initial production. In addition, colored light was observed that reflected the appearance of a structural color having a color corresponding to the average primary particle size of the inorganic spherical powder particles (b). Since the transmittance of light with a wavelength of 470 nm was high, the photocuring depth was high and the color compatibility was good.

[0153] As can be seen from the results of Comparative Example 1, the cured product of the curable composition in which the refractive index of the cured product of the monomer component M3 is greater than that of the inorganic spherical powder and particle F1 emits blue light against a black background, and has low transmittance for light with a wavelength of 470 nm, resulting in low photocuring depth and poor color compatibility.

[0154] As can be seen from the results of Comparative Example 2, in the case of the curable composition using the organic-inorganic composite powder CF1 not satisfying the above condition (D4), the filler settled in the curable composition (paste) in one out of five times, and the paste could not be discharged from the syringe container after six months of storage at 37°C. The evaluation results shown in the table are for this system.

[0155] As can be seen from the results of Comparative Example 3, the hardenable composition using monomer component M4, which exceeds the viscosity range specified in the present invention, has low fluidity as a hardenable composition (paste), and is found to have a fluidity that is not suitable for the bulk fill type flowable composite resin of the present invention.

[0156] As can be seen from the results of Comparative Example 4, in the case of the curable composition using the monomer component M5, which has a viscosity below the range specified in the present invention, the filler settled in the curable composition (paste) in one out of five times, and the paste could not be discharged from the syringe container after six months of storage at 37° C. The evaluation results shown in the table are for this system.

[0157] As can be seen from the results of Comparative Example 5, the cured product of the curable composition containing inorganic spherical powder F4 having an average primary particle size of less than 230 nm (outside the range specified in the present invention) emits blue light against a black background and has low transmittance of light with a wavelength of 470 nm, which results in low photocuring depth and poor color compatibility.

[0158] As can be seen from the results of Comparative Example 6, the cured product of the curable composition containing the irregularly shaped inorganic powder and particle F5 does not exhibit structural color, and therefore no colored light is observed against a black background, indicating that the color tone compatibility is poor.

[0159] Example 8 To 100 parts by mass of polymerizable monomer M1, 0.2 parts by mass of CQ, 0.3 parts by mass of DMBE, 0.4 parts by mass of DPIC, and 0.15 parts by mass of HQME were added and mixed to prepare a uniform polymerizable monomer composition. Next, 102 parts by mass of organic-inorganic composite powder CF2, 78 parts by mass of inorganic powder F1, and 6 parts by mass of rare earth metal fluoride powder FX1 were measured, and the above polymerizable monomer composition was gradually added under red light, and kneaded using a kneading machine planetary mixer (manufactured by Inoue Seisakusho) to obtain a uniform curable paste. Furthermore, this paste was defoamed under reduced pressure to remove air bubbles, and a polymerizable curable composition was produced. The obtained polymerization curable composition was filled into a syringe container, and (1) the fluidity immediately after production and after 6 months of storage at 37 ° C, (2) the consistency immediately after production and after 6 months of storage at 37 ° C, and (3) the discharge feeling immediately after production and after 6 months of storage at 37 ° C, (4) the photocuring depth of the curable composition (paste), (5) the light transmittance of the curable composition (cured product) at a wavelength of 470 nm, (6) the polymerization shrinkage stress, (7) the bending strength, (8) the visual evaluation of colored light, (9) the wavelength of colored light, (10) the visual evaluation of color tone compatibility, and (11) the X-ray contrast evaluation were performed. The composition of the curable composition (paste) is shown in Table 8, and the evaluation results are shown in Tables 9 to 11. The evaluation and measurement of the X-ray contrast properties were carried out by the methods described below.

[0160] (11) Measurement method for X-ray contrast The X-ray contrast of the cured product of the curable composition was measured by the following procedure. First, the curable composition was filled into a through hole (diameter 15 mm, through hole length 1.0 mm) provided in a polytetrafluoroethylene mold, and then both ends of the through hole were sealed by pressing with a polypropylene film. Next, light was irradiated in a state where a dental light irradiator (TOKUSO POWER LIGHT, manufactured by Tokuyama Corporation) was placed so as to be in close contact with the surface of the polypropylene film sealing the through hole opening. The positions of light irradiation were 5 positions (1 position at the center of the through hole and 4 positions on the inner side of the outer edge of the through hole) on one opening side of the through hole and 5 positions (1 position at the center of the through hole and 4 positions on the inner side of the outer edge of the through hole) on the other opening side. Then, light irradiation was performed for 20 seconds at each light irradiation position to obtain a cured product. The thickness of the obtained cured product was confirmed using a micrometer. Then, the cured product having a thickness of 1.0 mm ± 0.1 mm or less was used as a test piece to be used for measuring the X-ray contrast.

[0161] Next, an X-ray film (ultra-sensitive dental X-ray film, Kodak) was placed on a lead sheet with a thickness of 2.0 mm, and then a test piece and an aluminum step wedge with five different thicknesses (thickness: 1.0±0.01 mm, 2.0±0.01 mm, 3.0±0.01 mm, 4.0±0.01 mm, 5.0±0.01 mm) were placed on the X-ray film. Next, the test piece and the step wedge were irradiated with X-rays from a height of 40 cm from the surface of the X-ray film using an X-ray irradiator (PANPAS-E, YOSHIDA). The irradiation conditions were tube voltage: 60 kVp, irradiation time: 0.3 seconds. The X-ray film was then developed and printed on photographic paper. Next, the optical density of the test piece image and the step wedge image on the photographic paper was measured. Next, a calibration curve was created based on the five thicknesses of the step wedge and the optical densities corresponding to these five thicknesses, and the thickness of the step wedge (i.e., the aluminum material) at which the optical density of the test piece coincided with the optical density of the step wedge was determined based on this calibration curve. Then, when the optical density of an aluminum material with a thickness of 1 mm was taken as the reference (100 Al%), the value obtained by converting the determined aluminum material thickness into Al% was used as an evaluation index for X-ray contrast properties.

[0162] [Table 8]

[0163] [Table 9]

[0164] [Table 10]

[0165] [Table 11]

[0166] Examples 9 to 14 In Example 8, a curable composition was produced in the same manner as in Example 8, except that the composition of the curable composition was shown in Table 8, and the composition was filled into a syringe container. (1) Evaluation of fluidity immediately after production and after 6 months of storage at 37 ° C, (2) Evaluation of consistency immediately after production and after 6 months of storage at 37 ° C, and (3) Evaluation of discharge feeling immediately after production and after 6 months of storage at 37 ° C, (4) Evaluation of photocuring depth of the curable composition (paste), (5) Evaluation of light transmittance at a wavelength of 470 nm of the curable composition (cured product), (6) Evaluation of polymerization shrinkage rate, (7) Evaluation of bending strength, (8) Evaluation of colored light by visual observation, (9) Evaluation of wavelength of colored light, (10) Evaluation of color tone compatibility by visual observation, and (11) Evaluation of X-ray contrast were performed. The evaluation results are shown in Tables 9 to 11.

[0167] As can be seen from the results of Examples 8 to 14, the dental hardenable composition of the present invention, which contains a certain amount of rare earth metal fluoride powder (D2), shows little change in fluidity even after storage at 37°C for 6 months, and maintains the paste properties it had when first produced. In addition, colored light is observed that reflects the appearance of a structural color having a color corresponding to the average primary particle diameter of the inorganic spherical powder (b). Due to the high transmittance of light with a wavelength of 470 nm, not only is the photocuring depth high and the color compatibility good, but the composition also has high X-ray contrast properties and, while maintaining the fluidity that allows direct filling from a syringe, which is a characteristic of flowable CR, the formability is also improved as the fluidity decreases.

Claims

1. A monomer component (A) consisting of one type of radical polymerizable monomer or a mixture of multiple radical polymerizable monomers and having a viscosity at 25°C of 100 to 500 mPa s; one or more "spherical particle groups of the same particle size" (B) consisting of inorganic spherical powder or granules (b) having an average primary particle size of 230 to 500 nm as measured by an electron microscopy method, in which 90% or more of the total number of particles in the number-based particle size distribution of the powder or granules (b) are present within a range of 5% around the predetermined average primary particle size; and Photopolymerization initiator (C) Including, The number of "spherical particle groups of the same particle size" in (B) is a, and when a is 1, it is 1, and when a is 2 or more, it is a natural number from 1 to a. The "spherical particle groups of the same particle size" are classified into B in order of the smallest average primary particle size. m and the refractive index for the sodium d line at 25°C is n, Each B when the a is 2 or more m The first condition is that the average primary particle diameters of the particles differ from each other by 25 nm or more; and The refractive index of the cured body (AP) of the above (A): n (AP) And each B m The refractive index of the inorganic spherical powder (b) constituting the (Bm) When (Bm) Also, n (AP) <n (Bm) The second condition is that the relationship Satisfy both at the same time. The dental hardenable composition is a flowable composition capable of providing a hardened product that exhibits a structural color of a predetermined color tone independent of the angle of incidence of light, a part (B2F) of the inorganic spherical powder particles (b) which constitutes at least one type of "spherical particle group having the same particle size" constituting the (B) is contained in the dental curable composition as an organic / inorganic powder particle (B2) constituted of particles consisting of a complex in which the part of the inorganic spherical powder particles (B2F) is dispersed in a resin matrix (B2P); (B2F) contained in each organic-inorganic composite particle constituting (B2) is a part of inorganic spherical powder particles (b) constituting a single "spherical particle group of the same particle size", the average inorganic content defined by the total mass of (B2F) relative to the total mass of (B2) is 30 to 95 mass%, the median diameter in the volume-based particle size distribution of (B2) determined by a laser diffraction-scattering method is 1 to 30 μm and D90 is less than 35 μm, Among the components (B) contained in the dental curable composition, the inorganic spherical powder contained in a non-organic-composite state other than the component (B2F) is designated as (B1), and the refractive index: n of the monomer component (A) is changed to n (A) For each organic-inorganic composite particle constituting the (B2), the refractive index: n of the (B2F) contained therein is set to n (B2F) The refractive index of (B2P): n is n (B2P) When Regarding (B1), which n (Bm) Also, n (A) <n (Bm) The relationship is established, For all of the organic-inorganic composite particles constituting the (B2), n (AP) <n (B2F) Relationship and n (B2P) <n (B2F) The relationship is established, the total content of (B1) and (B2) is 150 to 300 parts by mass relative to 100 parts by mass of (A), and the proportion of (B2) to the total amount of (B1) and (B2) is within the range of 50 to 70% by mass; A dental hardenable composition comprising:

2. 2. The dental curable composition according to claim 1, further comprising 0.1 to 5 parts by mass of fine powder (D1) having an average primary particle diameter of 1 to 100 nm, as inorganic powder (D) composed of inorganic particles other than the constituent particles of (B), relative to 100 parts by mass of (A).

3. 2. The dental curable composition according to claim 1, further comprising a rare earth metal fluoride powder (D2) constituted by crystalline rare earth metal fluoride particles, having an average primary particle diameter of 1 to 300 nm measured by an electron microscope, and having a full width at half maximum of a maximum intensity peak derived from the crystalline rare earth metal fluoride of 0.3° or more in an X-ray diffraction pattern obtained by X-ray diffraction measurement, as an inorganic powder (D) consisting of inorganic particles other than the constituent particles of (B), wherein the amount of (D2) is 5 to 25 parts by mass relative to 100 parts by mass of (A), and the total content of (B1), (B2) and (D2) is 150 to 300 parts by mass relative to 100 parts by mass of (A).

4. 4. A dental composite resin comprising the dental curable composition according to claim 1, wherein the photocuring depth measured in accordance with JIS T6514:2015 is 3.5 to 5.0 mm, and the fluidity evaluated by the spreading diameter (mm) when a 0.1 g sample is placed in an area within a diameter of 5.5 mm on a horizontal glass plane and allowed to naturally spread at 37°C for 2 minutes is 4.0 to 12.0 mm.

Citation Information

Patent Citations

  • Hardened components for dental use

    JP6762623B2

  • Photocurable components

    JP6966785B2

  • Composite material, curable composition, and method for producing curable composition

    WO2020050123A1

  • X-ray opaque filler material, x-ray opaque dental filler material, method for producing x-ray opaque filler material, and curable dental composition

    WO2023042598A1